Secondary Hemophagocytic Lymphohistocytosis in COVID-19 - Jetty, Stephanie Lilia Pushpam; Noronha, Dotton Denis; Nayak, Akshatha; Dsouza, Altin (Annals of Pathology and Laboratory Medicine, 2021)
We present case of a 53-year-old lady who is a known case of rheumatoid arthritis and hypertension in Karnataka, South India, who presented with Severe Acute Respiratory Infection (SARI) like symptoms (fever, cough and breathlessness) due to COVID-19. During the course of treatment further investigations revealed evidence of Hemophagocytic Lymphohistocytosis (HLH). This case emphasizes the need for a thorough workup to identify the etiology of HLH as it may unmask a treatable entity in a COVID-19 patient.